Prevalence of visual impairment, refractive error and perinatal factors affecting visual impairment in children with cerebral palsy - Tian, Oo Kok (2020)
BACKGROUND: Cerebral palsy (CP) is the most common cause of physical disability in childhood, it occurs in 2-4.4/1000 population. The importance of visual perception in postural control and survival of patients with CP had been well documented. Early detection and treatment of ocular disorders is crucial. OBJECTIVE: To determine the prevalence of visual impairment and refractive error in children with cerebral palsy, and to evaluate aetiological factors affecting visual impairment in cerebral palsy children in Malaysia. METHODOLOGY: A cross sectional study was conducted in form of ophthalmology eye screening in three states in Malaysia adopting Key Informant Method (KIM) between November 2017 and June 2019. All children with cerebral palsy in Malaysia aged from 2 to 17 years old were included in this study. RESULTS: A total of 168 children were recuited from 3 states (Johor, Kelantan, Sarawak). The prevalence of visual impairment in children with CP in Malaysia was 61.9%. The most common ocular abnormality was refractive errors (74.4%), followed by cortical visual impairment (CVI) (30.4%), and strabismus (25%). Myopia (43.4%) was more common than hypermetropia (30.9% ), and exotropia (13.1 % ) was more common than esotropia (11.9% ). There was a statistical significant association between meningitis /encephalitis and visual impairment in children with CP (p=0.046). CONCLUSION: There is a high prevalence of visual impairment (61.9%) and refractive errors (74.4%) in children with cerebral palsy in Malaysia. There was a statistical significant association between meningitis /encephalitis and visual impairment in children with CP.